Antithrombin III and antivenom reversal of coagulopathy in rats envenomated with Malayan pit viper venom. - Pukrittayakamee, S; Clemens, R; Nontprasert, A; Desakorn, V; Charoenlarp, P; Chongsuphajaisiddhi, T; White, N (1994)
The therapeutic effects of antithrombin III (AT-III) and unrefined equine antivenom in the treatment of coagulopathy induced by Malayan pit viper (Calloselasma rhodostoma) venom were assessed in 42 adult Wistar rats. Following intramuscular venom injection (2 micrograms/g body weight), serial blood samples were taken from the femoral vein for measurement of whole blood clotting time and AT-III activity. There was progressive depletion of AT-III and blood ceased to clot a mean (S.E.) of 164 (8.3) min after venom injection. Coagulopathy was reversed by a high dose antivenom (10 micrograms/g) or a lower dose of antivenom (5 micrograms/g) in combination with AT-III (> or = 0.1 U/g; P < 0.01) but not 5 micrograms/g antivenom or AT-III alone. Following successful treatment, the mean plasma AT-III activity remained above 90%. In this animal model, systemic envenomation by the Malayan pit viper causes uncoagulable blood associated with AT-III consumption. The dose of antivenom required to reverse this coagulopathy can be reduced by half by the addition of AT-III sufficient to maintain blood concentrations within the normal range.